“E que tenhas o teu corpo!” testando empiricamente a existência de vieses temáticos no deferimento de habeas corpus pelos ministros do superior tribunal de justiça. - Pontes, Victor de Lemos (2022)
Is the nature of the crime (for which the habeas corpus patient is being prosecuted) a factor that influences the justices of the Superior Court of Justice (STJ) to deny the writ? The traditional constitutional and criminal procedural literature advocates that all individuals should be judged on an equal basis, without any distinction of treatment and without any other (meta)legal factor influencing the granting or denial of habeas corpus. However, for different reasons, without there being any commandment that advocates an inequitable treatment of certain cases, justices have been showing a selective behavior in the judgment of the aforementioned constitutional remedy. Some hypotheses were formulated, such as that crimes mostly committed by the most vulnerable strata of society tend to result in denial in the judgment of habeas corpus. For observation, a quantitative methodology was used, in which tools were used to verify judicial behavior, within the jurisdiction of the Superior Court of Justice (STJ), from 1989 to 2019, regarding the granting or denial of habeas corpus.